Syntapragmatics Representation of sentence in Kurdish Language - Khoshnaw Azeez Hama Ameen; Omar Mahmood Kareem (Zanco Journal of Humanity Sciences)
This study is devoted to syntapragmatics representation in forming syntactic structures, especially the simple sentences correlated to the context, because describing sentence structure in every language will be interpreted according to the phrases, structures representation system and these rules will be the indicators for the occurring and representing syntactic forms of a certain language which arise as a spontaneous process in the language. Therefore, this study determines the structure of the contextual sentences. It has been attempted to regularize those steps which by their implementation, the sentences structures such as; the minor units of syntactic components in utilizing and communication are constructed. In other words it is an attempt to explicate the elements and the levels of forming syntapragmatics structures.